Spiritual Intelligence Relationship with Organizational Citizenship Behavior and Commitment of School Teachers - shahmohammadi, Nayereh; Afzooni, Fayazallah (Journal of Medical and Psychological Trauma, 2018)
Introduction In an educational organization, because of its important function in human resources development and training in the community, respecting the values, spirituality, leadership, and management strengthening, based on spirituality and good citizenship behavior and commitment have greater importance. Aim This study examined the relation between spiritual intelligence with organizational citizenship behavior and organizational commitment of secondary school teachers. Methods The research method was correlational and its population included all teachers in education districts 2 and 5 in 2015 from which 358 teachers were selected by using Cochran formula and simple random sampling method as a sample. To collect data, three questionnaire: the King Spiritual Intelligence questionnaire (2007) and Padasakof et al. citizenship behavior questionnaire (2000) and organizational commitment questionnaire of Meyer (2001)were used .The reliability of the tools obtained by Cronbakh Formula 0/85,0/84, 0/7 respectively. For statistical analysis, the descriptive statistics (average, percentage, Standard deviation) and inferential statistical tests (Kolmogorov - Smirnov test, Pearson correlation coefficient test and stepwise regression analysis) were used. Conclusion The results showed that none of the components of citizenship behavior has a significant relation with a critical thought component of spiritual intelligence. Regarding the personal meaning making component of spiritual intelligence, only the components of sportsmanship and social customs have a significant relation, and other components have no significant association. All components of citizenship behavior are significantly associated with a transcendental consciousness component of spiritual intelligence and have no significant relation with self-awareness extends component. None of the organizational commitment components have a significant relation to the critical thinking component and high awareness of spiritual intelligence and only the emotional commitment of the organizational commitment component have a significant relation with the personal meaning making of spiritual intelligence, as well as with the expansion of consciousness component.
Keywords: spiritual intelligence; citizenship behavior; organizational commitment; high school teachers; Tehran.